La condizione giuridica della persona con disabilità: evoluzione, problemi e prospettive (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This essay analyzes the difficulties that can be found in the Italian legal system about the assessment of the legal condition of the disabled persons. These difficulties arise, especially, from the lack of a uniform definition of disability and an organic legislative regulation. There is a need to rethink the current legal system in a multidimensional perspective (shared in the international and supranational sources) in order to concretely guarantee that people with disabilities can live a life as autonomous (by enhancing their abilities) and independent (by supporting all the resources available on their territory) as possible. In this regard, the National Recovery and Resilience Plan and the recent draft law on disability are fundamental.
Keywords: People with disabilities; handicap; Code for the person with disabilities; National Recovery and Resilience Plan